2016
DOI: 10.1128/aac.00097-16
|View full text |Cite
|
Sign up to set email alerts
|

Single- and Repeated-Dose Pharmacokinetics of Ceftaroline in Plasma and Soft Tissues of Healthy Volunteers for Two Different Dosing Regimens of Ceftaroline Fosamil

Abstract: bCeftaroline fosamil (CPT-F) is currently approved for use for the treatment of complicated skin and soft tissue infections and community-acquired pneumonia at 600 mg twice daily (q12h), but other dosing regimens are under evaluation. To date, very limited data on the soft tissue pharmacokinetics (PK) of the active compound, ceftaroline (CPT), are available. CPT concentrations in the plasma, muscle, and subcutis of 12 male healthy volunteers were measured by microdialysis after single and repeated intravenous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…The achievement of therapeutic antibiotic concentrations at the infection site is an important consideration for breakpoint setting and dosing recommendations. In line with the PTA results presented here, comparison of ceftaroline PK following administration of ceftaroline 600 mg q12h or q8h in healthy volunteers found that calculated % fT >MIC values in the plasma, muscle and subcutis exceeded the S. aureus PK/PD targets for both dosage regimens up to an MIC of 2 mg/L, while the q8h dosage regimen provided % fT >MIC values ranging from 26.2%–43.0% across the three compartments for an MIC of 4 mg/L 32 …”
Section: Discussionmentioning
confidence: 55%
“…The achievement of therapeutic antibiotic concentrations at the infection site is an important consideration for breakpoint setting and dosing recommendations. In line with the PTA results presented here, comparison of ceftaroline PK following administration of ceftaroline 600 mg q12h or q8h in healthy volunteers found that calculated % fT >MIC values in the plasma, muscle and subcutis exceeded the S. aureus PK/PD targets for both dosage regimens up to an MIC of 2 mg/L, while the q8h dosage regimen provided % fT >MIC values ranging from 26.2%–43.0% across the three compartments for an MIC of 4 mg/L 32 …”
Section: Discussionmentioning
confidence: 55%
“…Further, higher doses of ceftaroline have often been prescribed (600 mg IV every 8 hours vs 12 hours). This higher dosing frequency is based on pharmacokinetic studies suggesting that every-8-hour dosing may optimize time-dependent killing in severe infections involving high bacterial inoculums [11, 12], although clinical data to support this approach are currently lacking.…”
mentioning
confidence: 99%
“…Nonetheless, even using an MIC of 2 μg/mL, the mean %fT N MIC in isolates from this cohort was 66.7%, which remains adequate for treatment. The AUC above MIC had a large range, representing the large interpatient variability of drug exposure, which has also been documented in the literature [22]. This is one of the reasons that the %fT N MIC is considered superior to the AUC above MIC.…”
Section: Discussionmentioning
confidence: 61%
“…1 μg/mL, the accepted MIC 90 of MRSA to ceftaroline [20]. This is above what is considered adequate for treatment [20][21][22]. MRSA isolates from all except one study subject had a measured MIC of 1 μg/mL or less.…”
Section: Discussionmentioning
confidence: 91%